Faktor-faktor yang berhubungan dengan pemeriksaan kehamilan (K4) pada ibu hamil trimester III di Puskesmas Sungai Pinang Kec. Sungai Pinang Kab. Ogan Ilir tahun 2023 - Pusdikawati, Devvi; Amlah, Amlah; Dhamayanti, Reffi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Health services for pregnant women (K4) in 2021 show that nationally it has reached the 2021 RPJMN target of 88.8% of the target of 85%. Assessment of the implementation of health services for pregnant women can be done by looking at the coverage of K1 and K4. Behavioral factors are influenced by three factors, namely: predisposing factors (which include age, occupation, education, knowledge and attitudes, enabling factors that are manifested in the physical environment and distance to health facilities, and reinforcing factors that are manifested in the support provided by families and community leaders. The purpose of this study was to determine the relationship between education, husband support and support from health workers simultaneously with K4 examination compliance at the Sungai Pinang Health Center, Sungai Pinang District, Ogan Ilir Regency in 2023. The study design used an analytic survey with a cross-sectional approach. The population in this study were all pregnant women in their third trimester. (gestational age more than 28 - 40 weeks) who came to check their pregnancies in June-July in the Work Area of the Sungai Pinang Community Health Center, Sungai Pinang District, Ogan Ilir Regency.The sampling technique in this study was carried out by means of purposive sampling with a total sample of 64 respondents. Collecting data using a questionnaire sheet. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study showed that there was a relationship between education (p value = 0.001), husband's support (p value = 0.006) and health worker support (p value = 0.000) with compliance with K4 examinations at the Sungai Pinang Health Center, Kec. Pinang River District. Ogan Ilir in 2023. It is hoped that the results of this research can be an illustration for the health center to be able to further increase the visits of pregnant women in their working areas by providing information to pregnant women about the schedule and benefits of pregnancy checks.